Say anything to anyone, anywhere - Cotton, Gayle (Wiley, 2013)
Includes index; Say Anything to Anyone, Anywhere gives readers five simple key guidelines to create rapport and organize strategies for success across different cultures. This book teaches to be proactive, not reactive, in your cross-cultural communications and shows how to use simple rapport tools to create trust with the cultures you work with or travel to. Learn how to organize productive interactions in person, on the phone, and by email. Discover interpersonal communication skills and virtual strategies that build strong relationships. Offers quick, accessible examples and clear guidelines about how to create an understanding between cultures Gives tips and strategies on how to communicate without offending